Fabrication of Silver-decorated Titanium Dioxide Nanofibers for Visible-light Photodegradation of Methylene Blue - Vasquez, Magdaleno R., Jr; Ramoy, Mary Raphael L.; Montallana, Arantxa Danielle S.; Montefalcon, Laika Jayne C. (E-journal of surface science and nanotechnology, 2025)
Visible light-mediated photocatalysis, which relies on the ability to absorb low-energy visible light, is a greener approach for degrading organic pollutants in water. Among the photocatalysts, titanium dioxide (TiO2) nanoparticles (NPs) are widely utilized because of their affordability, nontoxicity, large surface area, and strong photocatalytic properties. However, their effectiveness is restricted to the ultraviolet range, and recovery can be difficult when they are in NP form. Nanofibers, on the other hand, provide a similar high surface area and are simpler to recover. Additionally, coupling metal cations such as silver (Ag) to TiO2 extends the sensitivity to the visible light region, enhancing photocatalytic efficiency. In this work, electrospun TiO2 nanofiber mats (NFMs) were fabricated and decorated with Ag NPs. The TiO2 NFMs were designed for extended use and improved reusability in wastewater treatment, reducing the environmental risks associated with NP catalysts. Ag was introduced via wet impregnation with Ag nitrate and reduced to metallic Ag using plasma treatment. The plasma-treated Ag-TiO2 NFMs achieved 85% methylene blue removal from water under simulated solar irradiation, showing an 8% improvement in efficiency over TiO2. These results demonstrate the potential of Ag-TiO2 NFMs as an efficient and cost-effective solution to remove organic pollutants from wastewater under visible light irradiation.